Similar but different: ERP evidence on the processing of mental and physical experiencer verbs in Malayalam - Shalu, S.; Muralikrishnan, R.; Mathew, Anna Merin; Choudhary, Kamal Kumar (Frontiers in Language Sciences, 2026)
This study investigated the neurophysiological correlates of processing mental and physical subject experiencer verbs in Malayalam. Event-related brain potentials (ERPs) were recorded as 28 first-language speakers of Malayalam read intransitive sentences with the two types of experiencer verbs. Critical stimuli were either fully acceptable, whereby the subject case matched the requirements of the verb, or unacceptable, whereby the subject case violated the requirements of the verb. A linear mixed-models analysis confirmed negativity effects in the time window 400–800 ms for mental and physical experiencer verbs. Post-hoc analyses revealed that the negativity peaked relatively early for mental experiencer verbs, whereas relatively late for physical experiencer verbs. Further, the sentence-final acceptability of trials modulated the ERPs in non-anomalous conditions but not in violation conditions, and this modulation qualitatively differed between mental and physical experiencer verbs. These results suggest that, whilst a qualitatively similar mechanism is involved in the processing of both kinds of experiencer verbs, subtle but robust differences are inherent in processing mental vs. physical experiencer verbs in Malayalam.